PENGARUH MODEL THINK PAIR SHARE TERHADAP HASIL BELAJAR BAHASA INDONESIA PADA KURIKULUM MERDEKA MI QUR’ANIYAH - Baiq Esti Arini; Lukmanul Hakim; Aenullael Mukarromah (Fakultas Tarbiyah dan Keguruan, 2025)
This study aims to analyze the effect of the Think Pair Share (TPS) learning model on the Indonesian language learning outcomes of fourth-grade (Phase B) students at MI Qur’aniyah Batu Kuta within the context of the Merdeka Curriculum. The research employed a quantitative approach with a quasi-experimental design, specifically the non-equivalent control group design. The sample consisted of two classes, with 20 students as the control group and 19 students as the experimental group. The research instrument was a learning achievement test administered before (pre-test) and after (post-test) the treatment. Data were analyzed using normality, homogeneity, and independent sample t-tests with the assistance of SPSS 26. The results revealed a significant difference between students taught using the TPS model and those taught through conventional methods. The mean post-test score of the control group was 70.85, while the experimental group achieved 83.11, with a significance value of 0.001 < 0.05, indicating that the alternative hypothesis was accepted. Therefore, the application of the Think Pair Share model had a significant effect on improving students’ Indonesian language learning outcomes. Furthermore, the TPS model supports the implementation of the Merdeka Curriculum by encouraging independent thinking, active discussion, and effective collaboration among students.